Viability of milking and pajarete as agrotourism resources in the municipalities of Zapotlán el Grande and Gómez Farías, Jalisco (Mexico) - Martinez Ibarra, Jorge Arturo; Acosta Enciso, Jesús Javier; Grimaldo Anaya, Sofía (Cooperativismo & Desarrollo, 2022)
The present work has a diagnosis carried out in the municipalites of Zapotlán el Grande and Gómez Farías, Jalisco to identify the characteristics of the production and sale of pajarete (prepared with freshly milked cow’s milk, chocolate and alcohol) and the possibility of considering it as a potential agrotourism resource. The methodology used process of documentary investigation of municipal archives and records, field work, participant observation and semi-structured interviews with the producers. The results show the prevailing conditions in the stables; livestock management; the milking process and the sale of the birch to the public. It is concluded that the sale of the pajarete has complemented the economy of the small dairy producers and it is possible to consider it as a potential tourist resource, but making adjustments in the milking process, in the infrastructure and in the service to users.